Personal finance and investments : a behavioural finance perspective - Redhead, Keith, 1949- (London ; New York : Routledge, 2008)
In this book the author draws from finance, psychology, economics and other disciplines in business and the social sciences. Considerable attention is given to some subjects like: the psychology of investment decision-making, stock market bubbles and crashes, property investment, the use of derivatives in investment management, regulation of investments business. This book will help the readers to grasp the relevant principles of money management.
Includes bibliographical references (p. 856-889) and index.
nmn 13/05/13
Loans
Keywords: Investments; Finance, Personal; Investment analysis; Portfolio management